The Effectiveness of a Combined Intervention Approach for Improving Reading Fluency in Elementary School Students - Kuswardani, Hasna Pratiwi; Suprapti, Veronika; Paramita, Pramesti Pradna (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The ability to read plays a crucial role in the academic success and overall development of elementary school children. Unfortunately, many children in elementary school experience difficulties in reading, including issues with fluency, accuracy, and comprehension. These difficulties can lead to challenges in understanding the curriculum and result in lower academic achievement. To address this issue, a combined intervention approach was implemented, which combined repeated reading, listening while reading, error correction, and performance feedback methods. The aim of this intervention was to improve the accuracy aspect of reading fluency in elementary school children. This study used a single case experimental design with second-grade students as the research subjects. The development of children's reading abilities was measured using the Informal Reading Inventory. The results of the study indicate that the intervention provided was effective in improving the ability and fluency of reading in the research subjects.Kemampuan membaca memiliki peran yang sangat penting dalam kesuksesan akademik dan perkembangan secara keseluruhan pada anak-anak sekolah dasar. Sayangnya, banyak anak di sekolah dasar mengalami kesulitan dalam membaca, termasuk dalam hal kelancaran, akurasi, dan pemahaman bacaan. Hal ini dapat menyebabkan kesulitan dalam memahami kurikulum dan berakibat pada pencapaian akademik yang rendah. Untuk mengatasi masalah ini, diterapkan pendekatan intervensi gabungan dengan menggabungkan metode repeated reading, listening while reading, error correction, dan performance feedback. Tujuan dari intervensi ini adalah untuk meningkatkan aspek akurasi dari kelancaran membaca pada anak-anak sekolah dasar. Penelitian ini menggunakan desain eksperimen kasus tunggal dengan subjek penelitian adalah siswa kelas 2 sekolah dasar. Perkembangan kemampuan anak diukur menggunakan Informal Reading Inventory. Hasil penelitian menunjukkan bahwa intervensi yang diberikan efektif dalam meningkatkan kemampuan dan kelancaran membaca pada subjek penelitian.